Study of diffuse scattering on facial surface using ray tracing approach - Po-Yen Lai; Ray Jia Hong Ng; Tatsuya Omotezako; Huizhe Liu; Wenjun Ding; Lim Jiun Yeu; Akira Matsubara (Scientific Reports)
Abstract This study investigates the role of topographic attributes in light scattering and diffuse reflection on the skin surface, and diffuse transmission across the surface layer. Validated ray-tracing simulations establish a quantitative link between subvisible micro texture (SMT) and macro texture to skin optical properties, representing youthful and healthy skin characteristics. Our findings reveal the dominant role of the subvisible micro texture parameter ( $${u}_{w}/{u}_{h}$$ , the ratio of width to height) in governing light scattering. Smaller ratios, corresponding to fine SMT, result in increased diffuse reflection and create a more pronounced soft-focus effect, which plays a critical role in driving profound skin appearance such as radiance. While the macro texture parameter also influences scattering, its impact is less significant. Additionally, we quantify the impact of SMT on the transversal light movement from inside the skin to outside it. This simulation showed that more incident light leaves after traveling inside skin with smaller $${u}_{w}/{u}_{h}$$ , a measure of finer SMT. Our validated 2D subvisible micro texture model accurately computes the light-skin interactions influenced by the various levels of the skin’s topographic features, offering valuable insights for cosmetics, dermatology, and aesthetic medical imaging.